Kecenderungan Masyarakat dalam Konsumsi Produk Patiseri Sehat dan Kaitannya dengan Perkembangan Bisnis Patiseri - Maulina, Lien; Sufianti, RD Arti (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The increasing public awareness of healthy living has significantly influenced consumption patterns, particularly in the patisserie sector. This study explores the tendencies of the community in consuming healthy patisserie products and their implications for the development of the patisserie business in Bandung. Using a qualitative approach, this research is based on library research and literature review to analyze the correlation between consumer preferences and the growth of the patisserie industry. Findings indicate a rising demand for health-conscious patisserie products driven by lifestyle changes, urbanization, and increased knowledge of nutrition. The study also identifies challenges faced by patisserie businesses in adapting to this trend, such as the need for innovative ingredients and sustainable practices. Furthermore, it highlights how these businesses capitalize on consumer preferences through product differentiation and marketing strategies. This research contributes to the understanding of consumer behavior in the context of healthy food trends and offers insights into strategies for patisserie businesses to thrive in an increasingly health-conscious market. The findings underscore the importance of aligning business strategies with consumer needs to achieve sustainability and long-term growth.